Direct access to α, α′-diarylated ketones through N-heterocyclic carbene-catalyzed 1, 6-addition of aromatic aldehydes to para-quinone methides. Issue 8 (18th April 2017) - Zhang, Guifu; Jiang, Longxiang; Shi, Wenjuan; Zhou, Meiling; Qiu, Fenghao; Sun, Shaofa; Wang, Jian; Guo, Haibing
ABSTRACT: N -Heterocyclic carbene-catalyzed 1, 6-addition of aromatic aldehydes to para -quinone methides has been developed. This method could efficiently furnishα, α ′-diarylated ketones with good to high yields, which contain various functional groups. GRAPHICAL ABSTRACT: